rdlc 2017
DOI: 10.7764/rdlc.16.3.361
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of the study into water consumption in energy audits in schools

Abstract: The approach of energy audits usually disregards the study of water as it considers that the supply does not involve energy consumption within the building. This paper aims to make visible both the energy footprint involved in ensuring safe water for human consumption and the collection and treatment of waste water. Furthermore, a methodology for conducting an energy audit is shown for the study of water consumption and applies it to a school to verify whether the measures proposed to reduce the consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…De hecho, ya hay autores que han abordado la vinculación del agua con la energía (16), la relación entre agua y energía y entre agua y emisiones de gases de efecto invernadero, destacando su importancia a escala urbana (17), y la utilización de energía a lo largo de los grandes sistemas de infraestructura convencionalmente utilizados para la captación, transporte y distribución de agua, además de para el tratamiento de las aguas usadas (18,19,20). consumo de agua y coste de dicho consumo.…”
Section: Introductionunclassified
“…De hecho, ya hay autores que han abordado la vinculación del agua con la energía (16), la relación entre agua y energía y entre agua y emisiones de gases de efecto invernadero, destacando su importancia a escala urbana (17), y la utilización de energía a lo largo de los grandes sistemas de infraestructura convencionalmente utilizados para la captación, transporte y distribución de agua, además de para el tratamiento de las aguas usadas (18,19,20). consumo de agua y coste de dicho consumo.…”
Section: Introductionunclassified
“…The educational sector is by no means unaffected by the crisis and soaring costs and generally accommodate large number of people during the daytime and place a substantial burden on the grid and harbour substantial inefficiencies (Sanchez-Torija et al, 2017;Samuels and Booysen, 2019). A study (Van der Berg et al, 2011) reported on how the low quality of education provided in schools within disadvantaged communities can lead to exclusion and marginalisation, limiting the future prospects of learners from a young age (Van der Berg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of existing research on urban water demand management have focused on the residential sector, for example, demand forecasting (Adamowski et al, 2012;Bougadis et al, 2005;Donkor et al, 2012;Ghiassi et al, 2017;Ren and Li, 2016), demand modelling (Gurung et al, 2014;Jacobs and Haarhoff, 2004), general demand management (Kenney et al, 2008), and water usage management interventions (Datta et al, 2015;Dernoncourt and Lee, 2016;Fielding et al, 2012). There is limited research on the water demand in the non-residential or educational sectors despite the fact that these sectors can be high water consumers (Sánchez-Torija et al, 2017). Moreover, although historic water usage data has been used in several studies to model water usage patterns, there are several influential factors including socio-economic, political and climatic variables that have not been specifically taken into consideration (Botai et al, 2017;Donkor et al, 2012;Enqvist and Ziervogel, 2019;Muller, 2018;Scheba and Millington, 2018).…”
Section: Introductionmentioning
confidence: 99%